Bilateral Extramural Ectopic Ureter in a Bitch - Correction by Ureteroneocystostomy - do Nascimento Medeiros, Brenda Lurian; Galeno, Lygia Silva; Vargas da Silva, Thiago; Ximenes Silva, Alana Larissa; Lustosa Rodrigues Camapum, Jaqueline; Martins Araújo, Bruno; Lima Silva, Francisco; Campos Rodrigues, Marcelo (Acta Scientiae Veterinariae, 2024)
Background: Ectopic ureter is a congenital abnormality that may be bilateral or unilateral and affects mainly young animals of both sexes, in which the ureter does not drain naturally into the trigone of the bladder. This is due to the abnormal differentiation of the mesonephric and metanephric ducts in the embryonic stage. The most common clinical signs are incontinence and urinary infection. This case report describes the surgical technique of ureteroneocystostomy (UNC), as well as the postoperative therapeutic approach in a case of bilateral extramural ectopic ureter in a bitch Pitbull. Case: A 10-month-old bitch Pitbull, weighing 31 kg, with a 6-month history of pollakiuria, urinary incontinence and recurrent urinary infection was diagnosed with an extramural ectopic ureter by means of excretory urography. Preoperative tests included complete blood count, biochemical parameters (ALT, albumin, urea, creatinine, calcium, phosphorus), urinalysis, urine culture and antibiogram, urinary protein creatinine (UPC) ratio and abdominal ultrasound. After completing the complement tests, the patient was subjected to surgery to correct the anatomical course of her ureters, using the ureteroneocystostomy technique. The patient received general inhalation anesthesia, a median celiotomy was performed from the xiphoid cartilage to the pubis, and the ureters were identified. Both ureters were found to be inserted in the urethra, so their distal portion was tied off with 3-0 polydioxanone suture. After this, a cystotomy was performed to implant the ureters in the region of the vesical trigone by suturing them into the bladder mucosa with 5-0 polydioxanone suture in a simple interrupted pattern. This procedure was initially performed on the left ureter, which was dilated, followed by the right ureter, which was normal. Cystorraphy was performed using two suture patterns, a simple continuous pattern and a Cushing pattern with 3-0 polydioxanone suture. Cheilorrhaphy was performed using nylon suture in a sultan pattern, the subcutaneous tissue was closed in a simple continuous pattern using 3-0 polydioxanone suture and the skin in a wolf pattern using 3-0 nylon suture. The patient remained hospitalized for 48 h postoperatively, presenting good evolution of healing. Signs of urinary incontinence persisted for a week after surgical intervention, thereafter gradually returning to normality. Two months after the surgical procedure, the patient underwent a new excretory cystourethrography, which showed bladder fullness and normal topographical anatomy of the ureters. Discussion: Ureteral ectopy is the most frequent cause of urinary incontinence in puppies, especially females. Although the history and clinical signs of a patient lead to suspicion of ectopic ureter, imaging tests are indispensable for diagnostic confirmation. In the patient of this case report, an excretory urography was essential to locate the urethral termination and insertion, thus allowing the urethral ectopy to be classified as extramural. The surgical technique selected here was ureteroneocystostomy, which allowed the proper insertion of the ureters into the urinary bladder in anatomical topography, followed by a satisfactory response in urinary continence and bladder fullness, despite urinary incontinence in the postoperative period. Factors such as early diagnosis, functional viability of the urinary tract, application of the appropriate surgical technique and strict postoperative management were essential for the therapeutic success of the ectopic ureter surgery. It was concluded that the ureteroneocystostomy technique with transverse transection for the correction of extramural ectopic ureter was a satisfactory procedure, proving to be feasible and adequate for restoring normal urinary flow. Keywords: bladder trigone, urinary incontinence, urinary infection. Título: Ureter ectópico extramural bilateral em cadela - correção por ureteroneocistostomia Descritores: trígono vesical, incontinência urinária, infecção urinária.